2000
DOI: 10.1108/eum0000000005306
|View full text |Cite
|
Sign up to set email alerts
|

Design, coordination and control of hybrid factories

Abstract: In this paper, the authors elaborate the notion of a hybrid factory: factories in which some production capacity is dedicated to process-oriented manufacturing, and some is dedicated to product-oriented manufacturing. We present the results of a field study of one such factory and, using it as an example, develop a list of eight issues that may arise as a part of implementing and managing a hybrid factory. Where possible, we tie these issues into existing research streams. We show how our field site addressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…capacity management, line balancing, set-up time reduction, mixed-model production; see Monden, 1983) could be customised to increase the usage of productive assets in this species. Similarly, the recommendations and research directions for the design, co-ordination and control of hybrid factories identified by Doerr and Magazine (2000) apply to this species.…”
Section: Directions For Manufacturing Innovationsmentioning
confidence: 99%
“…capacity management, line balancing, set-up time reduction, mixed-model production; see Monden, 1983) could be customised to increase the usage of productive assets in this species. Similarly, the recommendations and research directions for the design, co-ordination and control of hybrid factories identified by Doerr and Magazine (2000) apply to this species.…”
Section: Directions For Manufacturing Innovationsmentioning
confidence: 99%
“…Bullinger and Sauer [6] changed the number of production system resources to be optimised until obtaining a state judged satisfactory. Other authors performed simulation studies system design [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…This would require developing the capacity to manufacture both components in both plants. This investment in production capability at both plants for both components should reduce shipping costs and generate greater responsiveness/flexibility to market (see Doerr and Magazine 2000).…”
Section: Introductionmentioning
confidence: 99%